Analysis of Economic Waste Management in Medan City - Purba, Bonaraja; Sinurat, Nurlia Aprianti; Angkat, Febryanti (Peneliti.net, 2023)
Waste management is becoming an increasingly important issue in the context of sustainable development. Waste refers to residual material that becomes useless after use. Organic waste originates from living organisms and can naturally decompose, while inorganic waste is unusable and difficult to decompose. Effective waste management is crucial in reducing environmental impacts and improving the quality of life. This study focuses on analyzing the economic aspects of waste management in Medan City using qualitative methods and secondary data. The results indicate that waste management in Medan faces various challenges. Community participation and technological use can be solutions to address waste-related issues